The Biosafety Research Road Map: the search for evidence to support practices in the laboratory — SARS-CoV-2 - Blacksell, SD; Dhawan, S; Kusumoto, M; Le, KK; Summermatter, K; O'Keefe, J; Kozlovac, J; Almuhairi, SS; Sendow, I; Scheel, CM; Ahumibe, A; Masuku, ZM; et al. (Mary Ann Liebert, Inc. Publishers, 2023)
Introduction: The SARS-CoV-2 virus emerged as a novel virus and is the causative agent of the COVID-19 pandemic. It spreads readily human-to-human through droplets and aerosols. The Biosafety Research Roadmap aims to support the application of laboratory biological risk management by providing an evidence base for biosafety measures. This involves assessing the current biorisk management evidence base, identifying research and capability gaps, and providing recommendations on how an evidence-based approach can support biosafety and biosecurity, including in low-resource settings.